2019
DOI: 10.12688/f1000research.19484.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of benefits and harms of surgical treatments for post-radical prostatectomy urinary incontinence: a systematic review and meta-analysis protocol

Abstract: Background: Post-radical prostatectomy urinary incontinence (PPI) is a frequent and feared complication that can affect approximately 25% of patients. Between 1 and 10% of patients suffering from PPI will require surgery. The effectiveness of the available surgical interventions has only been compared in a few randomized controlled trials and the available reviews have important limitations regarding both benefits and harms that make them insufficient to inform decision-making. The aim of the study is to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Thus, shared decision making between the patient and his treating physician is an important perioperative criterion that strongly correlates with patients' long-term acceptance of the surgical procedure. In addition to the intended impact of radical prostatectomy on the oncological outcomes, this procedure clearly has a functional component, resulting in stress urinary incontinence (in varying degrees) and erectile dysfunction in some of the surgically treated patients, leading to a significant impact on the quality of life [22][23][24]. For this reason, perioperative pelvic floor muscle training should be offered to patients by urologic centers, and therapeutic counselling should be offered to patients with postoperative erectile dysfunction problems in an outpatient setting [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, shared decision making between the patient and his treating physician is an important perioperative criterion that strongly correlates with patients' long-term acceptance of the surgical procedure. In addition to the intended impact of radical prostatectomy on the oncological outcomes, this procedure clearly has a functional component, resulting in stress urinary incontinence (in varying degrees) and erectile dysfunction in some of the surgically treated patients, leading to a significant impact on the quality of life [22][23][24]. For this reason, perioperative pelvic floor muscle training should be offered to patients by urologic centers, and therapeutic counselling should be offered to patients with postoperative erectile dysfunction problems in an outpatient setting [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…A recently published systematic review and metaanalysis by Choiniere et al identified 20 trials of fixed and adjustable male urethral slings including 1,956 patients, which identified an overall cure rate (defined as using <1 pad per day) of 58.6% (24). These results are similar to a review by Meisterhofer et al comparing fixed and adjustable slings, which identified that whilst adjustable slings may yield a higher cure rate, they may be associated with higher rates of complication and explantation (25).…”
Section: Selection Processmentioning
confidence: 99%
“…In contemporary practice, surgical interventions for PPUI encompass four principal methods: bulking agents, male synthetic slings, compressive balloon systems (also known as ProACTTM), and the artificial urinary sphincter (AUS), which stands as the current gold standard. 31 It is crucial to distinguish between bladder instability, prevalent in the early postoperative period, and intrinsic sphincter dysfunction, responsible for persistent stress incontinence. The latter does not respond to physiotherapy and anticholinergic medication.…”
Section: Surgical Treatmentmentioning
confidence: 99%